HnRNPM modulates alternative splicing in germ cells by recruiting PTBP1 - Peng Lv; Wenchao Xu; Sheng Xin; Yuanxuan Deng; Bin Yang; Dengjianyi Xu; Jian Bai; Deilin Ma; Tao Wang; Jihong Liu; Xiaming Liu (Reproductive Biology and Endocrinology)
Abstract Background Heterogeneous nuclear ribonucleoprotein M (HnRNPM) is a key splicing factor involved in various biological processes, including the epithelial‒mesenchymal transition and cancer development. Alternative splicing is widely involved in the process of spermatogenesis. However, the function of hnRNPM as a splicing factor during spermatogenesis remains unknown. Methods The expression of hnRNPM in germ cells at different stages was detected by polymerase chain reaction, western blotting, a single-cell database, and chromosome spreading assays. Conditional hnRNPM knockout mice were generated to observe the development of testes and germ cells in male mice. Histological staining, immunofluorescence staining and transmission electron microscopy were used to observe the abnormal development of sperm from conditional hnRNPM-deficient mice. Coimmunoprecipitation and mass spectrometry analyses revealed the proteins that interact with hnRNPM. RNA sequencing was performed to analyse the different alternative splicing events in the testes of control and hnRNPM-deficient mice. Results In this study, we revealed that hnRNPM is highly expressed in spermatocytes and round spermatids, with the exception of XY bodies and metaphase. Therefore, we generated a germ cell-specific hnRNPM conditional knockout mouse model to investigate the role of hnRNPM in spermatogenesis. A lack of hnRNPM led to male infertility under natural conditions. Male hnRNPM-deficient mice presented lower numbers of sperm, lower motility, significantly more malformed sperm and even tailless sperm. Moreover, we found that hnRNPM interacted with PTBP1 to collectively regulate the process of spermatogenesis. In addition, we found that hnRNPM deficiency caused 1617 different alternative splicing events, and we detected abnormal exon skipping events in Cep152, Cyld, Inpp4b and Cd59b. Conclusions Together, our results suggest that hnRNPM regulates the alternative splicing of mRNAs during spermatogenesis by recruiting PTBP1 and is required for male mouse fertility.